Mycena yuezhuoi sp. nov. (Mycenaceae, Agaricales), a purple species from the peninsula areas of China - Liu, Zewei; Na, Qin; Cheng, Xianhao; Wu, Xiaoming; Ge, Yupeng (Phytotaxa, 2021)
During a study of Mycena s.l. in eastern China, a distinct species, Mycena yuezhuoi, was collected on the Jiaodong Peninsula. Mycena yuezhuoi has the following characteristics: a purple pileus, emarginate and white lamellae, elongated pip-shaped to cylindrical basidiospores, and cheilocystidia that are smooth or occasionally have an apical protrusion. The discovery of M. yuezhuoi provides new material for the study of Mycena sect. Calodontes, especially the M. pura complex. Although M. yuezhuoi closely resembles M. pura regarding macroscopic characteristics, it forms a monophyletic clade in phylogenetic trees that is distinct from clades in the M. pura complex. Moreover, the molecular phylogeny obtained from a combined analysis of multiple gene regions (ITS+RPB1+tEF1) supports the results of the morphological identification. We propose Mycena yuezhuoi as a new species based on morphological observations and phylogenetic analyses and provide line drawings, photos, descriptions, and comparisons with allied species.